PENGEMBANGAN MODUL KORBAN BENCANA PADA APLIKASI SIKEMBAR BERBASIS WEB - Zahidan Ardhiansyah; Isram Rasal (Jurnal Riset Sistem Informasi, 2025)
This study discusses the development of the Disaster Victim Module in the SiKembar (Sistem Informasi Keluar Masuk Barang) web-based application. The development of this module aims to optimize data management of disaster victims and aid distribution during natural disasters, specifically within the Cianjur Regency area. The module is designed with three main features: aid submission, aid distribution, and victim data collection. The research adopts a web-based software development method using PHP programming language and the CodeIgniter framework. The developed module is directly integrated into the existing SiKembar system and tested using the black-box testing method to ensure that all functionalities operate as expected. Based on internal testing results, the system is capable of facilitating the data collection, aid application, and distribution processes in a more structured and efficient manner. Development results demonstrate the potential to enhance the effectiveness of data management and post-disaster aid coordination in a systematic and responsive manner within the BPBD of Cianjur Regency